Understandings of the AI business ecosystem in South Korea: AI startups' perspective - Jinyoung Nam; Junghwan Kim; Yoonhyuk Jung (International Telecommunications Society (ITS), 2023)
Artificial intelligence (AI) startups are utilizing artificial intelligence technology to produce novel solutions across a multitude of sectors, becoming key players in the AI business ecosystem, signifying AI business networks consisting of technology, business applications, and various industry sectors. Particularly noteworthy is the substantial surge in the initiation and investment in AI startups within South Korea. To gain insight into the AI business ecosystem, this study explores how the ecosystem is collectively understood from AI startups' perspectives in South Korea. We conducted semi-structured interviews with 16 CEOs and managers in AI startups in South Korea. This study conducted a core-periphery analysis of the social representation of the AI business ecosystem. By doing so, it bridges an existing knowledge gap and enriches the body of research related to the AI business ecosystem, as well as the current opportunities and challenges it faces. Our findings not only inform and guide practitioners, governments, and businesses alike, but also suggest that continuous discussion among government agencies, large tech companies, and AI startups is crucial for establishing a more sustainable AI business ecosystem.
Keywords: 330; Artificial intelligence (AI); AI startups; AI business ecosystem; Social representations theory